Flexible, water-proof, wire-type supercapacitors integrated with wire-type UV/NO2 sensors on textiles - Kim, Daeil; Keum, Kayeon; Lee, Geumbee; Kim, Doyeon; Lee, Sang-Soo; Ha, Jeong Sook (ELSEVIER SCIENCE BV, 2017)
Wire-type devices that can be integrated onto fabrics are being actively studied to meet the demands for various wearable systems. In this study, we report the fabrication of wire-type supercapacitors (WSCs) integrated with wire-type UV/NO2 sensors on textiles. The WSC consists of braided carbon fiber electrodes coated with multi-walled carbon nanotubes (MWNT)/V2O5 nanowires(NWs), a cellulose-based separator, and an ionic-liquid-based electrolyte of [EMIM][TFSI]/LiCl/Al2O3 nanoparticles. This fabricated WSC exhibited good performance with an extended potential window of 1.5 V and areal capacitance of 10.6 mF/cm(2) at 0.5 mA/cm(2). Very stable electrochemical performance of the WSC was also observed under mechanical deformations of bending, knotting, and folding. In addition, stable WSC performance in water was demonstrated by encapsulation with a thermally-shrinkable tube. Furthermore, mu-light-emitting diodes and wire-type NO2 gas and UV sensors were operated by the integrated multiple WSCs on a textile: The MWNT-coated wool wire detected NO2 gas reproducibly by increase of the current. Using spiropyran and ZnO NWs, changes in both color and photocurrent were detected upon UV irradiation. This work demonstrates the great potential of our WSC for use in wearable textile sensor systems as an efficient energy storage device.
Keywords: HIGH-ENERGY DENSITY; STATE YARN SUPERCAPACITORS; ALL-SOLID-STATE; HIGH-PERFORMANCE; SHAPED SUPERCAPACITORS; GRAPHENE FIBERS; CARBON; OXIDE; ELECTRODES; PRISTINE